Influência da geometria de reatores UASB em escala unifamiliar sobre seu desempenho no tratamento de esgoto - Santos, Silvânia Lucas dos (2016)
In this research a modified design of anaerobic UASB type reactors is proposed for sewage treatment at a single-family scale, with differentiated geometry. The robustness of these systems was investigated, when subjected to hydraulic loads similar to those usual in residences and the influence of temperature on anaerobic digestion. The experimental system consisted of 6 reactors UASB all with a useful volume of 240 L but having differentiated geometry: three had a diameter of 0.3 m in the digestion zone and three 0.4 m. Parallel to these systems a modified reactor with a lateral decanter (UASB-Y) and a conventional UASB reactor, also with 240 L, were operated. To assess the influence of temperature on anaerobic digestion, 4 UASB-Y reactors were used each with a volume of 25 L. The effect of temperature on the efficiency of the treatment was investigated for temperatures ranging from 25 to 12 ° C. The obtained results showed that, for the imposed operating conditions (mean hydraulic retention time of 12 and 6 hours), all the modified reactors presented COD removal efficiencies of more than 65%. Analysis of variance (ANOVA) confirmed that there was no significant difference in the removal efficiency for the different tested reactors, so that other criteria such as installation cost, operation and reactor height should be considered in the choice of treatment unit, according to the characteristics of the soil where they will be installed. The variations in flow peaks indicated that the modified reactors are robust and support a peak flow equivalent to 40% of the their treatment capacity, without great damage to the treatment system. The results showed that the efficiency of the treatment decreases with the temperature, mainly due to the inefficiency of the hydrolysis, when the reactors were temperatures below 25°C. In this way, it was concluded that the proposed UASB reactors, can effectively treat sewage from a family, in a unit of 240 L, reaching greater efficiency than reported for septic tanks systems, having good operational stability and recovery capacity, after application of hydraulic shocks similar to those produced in residences.